An intensive swallowing exercise protocol for improving swallowing physiology in older adults with radiographically confirmed dysphagia - Balou M (Dove Medical Press, 2019)
Matina Balou,1 Erica G Herzberg,2 David Kamelhar,3 Sonja M Molfenter4 1Department of Otolaryngology, New York University School of Medicine, Head & Neck Surgery, New York, NY, USA; 2Department of Speech-Language Pathology, New York University Langone Health, Rusk Rehabilitation, New York, NY, USA; 3New York University School of Medicine, Department of Pulmonary Medicine, New York, NY, USA; 4Department of Communicative Sciences and Disorder, Communicative Sciences and Disorders, New York University Steinhardt, New York, NY, USA Purpose: The aim of this study was to investigate improvements in swallowing function and physiology in a series of healthy older adults with radiographically confirmed dysphagia, following completion of an exercise-based swallowing intervention.Patients and methods: Nine otherwise healthy older adults (six females, mean age =75.3, SD =5.3) had confirmed impairments in swallowing safety and/or efficiency on a modified barium swallow study. Each participant completed an 8-week swallowing treatment protocol including effortful swallows, Mendelsohn maneuvers, tongue-hold swallows, supraglottic swallows, Shaker exercises and effortful pitch glides. Treatment sessions were conducted once per week with additional daily home practice. Penetration–Aspiration Scale and the Modified Barium Swallowing Impairment Profile (MBSImP) were scored in a blind and randomized fashion to examine changes to swallowing function and physiology from baseline to post-treatment.Results: There were significant improvements in swallowing physiology as represented by improved oral and pharyngeal composite scores of the MBSImP. Specific components to demonstrate statistical improvement included initiation of the pharyngeal swallow, laryngeal elevation and pharyngeal residue. There was a nonsignificant reduction in median PAS scores.Conclusion: Swallowing physiology can be improved using this standardized high-intensity exercise protocol in healthy adults with evidence of dysphagia. Future research is needed to examine the individual potential of each exercise in isolation and to determine ideal dose and frequency. Studies on various etiological groups are warranted. Keywords: dysphagia, modified barium swallow, rehabilitation, deglutition, exercise, presbyphagia